Desenvolvimento de partograma digital para acompanhamento de trabalho de parto - Ramos, Talyta Soares de Vasconcelos (2022)
Each year, about 3 million births take place in Brazil, involving almost 6 million people, with about 98% of them taking place in hospitals, whether public or private. The model of care at birth that prevails in recent decades is characterized by the routine use of obstetric practices that are sometimes iatrogenic. In this sense, the World Health Organization (WHO) recommends the use of the partograph to monitor labor since 1994 with the aim of improving care and reducing maternal and fetal morbidity and mortality. The partogram consists of the graphic representation of labor and is a communication tool that facilitates immediate knowledge of its evolution. The objective of the present work was to develop a digital partogram in the form of an application for use on a cell phone or tablet, since studies have shown that some health professionals who work in labor were not using the physical partogram for several reasons, among them, the lack of motivation to fill in the information. The application will serve as a tool for discussing clinical cases by the health team, teaching students who are in this environment, in addition to assisting in the management and monitoring of patients in a delivery room, where there are often multiple patients in labor concurrently. The device also allows sharing the exam/partogram of each patient, as well as allowing the printing of the exam so that it can be attached to the printed medical record of the health service. The device has some points that will be improved, such as the creation of reassessment alerts, implementation of the device on digital platforms so that it can be acquired, and the development of the application for the iOs operating system, allowing a greater number of people to have access of the tool.